Rich and Poor Households in Poland’s Credit Market — A Comparative Analysis for the Years 2000–2013 - Wałęga, Agnieszka; Wałęga, Grzegorz (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2016)
Today intertemporal substitution of consumption is done by using the credit market on a large scale. The main factor determining both consumption and the ability to borrow is household income. The aim of the article is to examine the extent to which low- and high-income consumers use credit. The factors that influence the likelihood of being in debt were identified. The burden of debt repayment on household budgets depends on affluence. Non-identifiable data from the household budget survey from the years 2000–2013 and data from the study „Social Diagnosis” were used in the paper. To verify the research problems, structure analysis and regression modeling were used, taking into account model for binomial variables. The results of the study indicate that wealthy and poor households use loans in different ways, a fact reflected in the variation in the structure of consumption. In the period analysed, there was a noticeable increase in the burden of repayments of loans on the budgets of households with high incomes. The results of the study indicate that income, education and place of residence determine to the greatest extent the use of the credit by households.